Standardized Nursing Language (SNL) Application in Diverse Nursing Practice and Documentation Settings - Dwi Wahyuni, Erna; Nursalam, Nursalam; Setiya Dewi, Yulis (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Effective communication in healthcare is crucial, and Standardized Nursing Language (SNL) has emerged as a powerful tool to enhance nursing practice and documentation. However, disparities in SNL awareness and knowledge pose challenges to its effective implementation. This systematic review aims to synthesize research on SNL application in nursing practice across diverse settings, utilizing a comprehensive database search and predefined criteria for study selection.   Methods: Comprehensive searches were conducted across databases like PubMed, Scopus, ProQuest, and Web of Science. This systematic review adhered to the updated guidelines provided by PRISMA 2020. Three independent reviewers assessed study eligibility based on predefined criteria, resolving discrepancies through discussion. A narrative synthesis approach categorized and thematically analyzed the data, focusing on SNL's impact in diverse healthcare settings. Data was retrieved after the studies were subjected to quality assessment and risk of biases.   Results: The review included twelve studies spanning various healthcare systems and regions. While SNL demonstrated potential benefits, disparities in awareness, knowledge, and utilization were evident among participants. Challenges such as complex documentation processes and feasibility concerns were raised.   Conclusion: SNL plays a pivotal role in enhancing nursing practice, improving documentation, and facilitating effective communication. Addressing education gaps and providing ongoing training opportunities are essential to overcome implementation challenges. Collaboration among healthcare institutions, educators, and regulatory bodies is crucial to fully leveraging SNL's benefits for better patient care and healthcare outcomes.